2013
DOI: 10.1371/journal.pone.0057156
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed miRNAs after GnRH Treatment and Their Potential Roles in FSH Regulation in Porcine Anterior Pituitary Cell

Abstract: Hypothalamic gonadotropin-releasing hormone (GnRH) is a major regulator of follicle-stimulating hormone (FSH) secretion in gonadotrope cell in the anterior pituitary gland. microRNAs (miRNAs) are small RNA molecules that control gene expression by imperfect binding to the 3′-untranslated region (3′-UTR) of mRNA at the post-transcriptional level. It has been proven that miRNAs play an important role in hormone response and/or regulation. However, little is known about miRNAs in the regulation of FSH secretion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 49 publications
1
49
0
2
Order By: Relevance
“…In our in silico prediction, we observed that several miRNAs were assigned to gene ontology processes termed as ''GnRH signaling pathway'' (among others). Previous studies have proven the effect of miRNA in GnRH signaling and also the effect of GnRH signaling in miRNA expression patterns (55)(56)(57)(58). The potential gene targets related to this process included kinases and calcium and MAPK signaling pathways, which are involved in FSH and LH production, which in turn could be affecting proper timing for oocyte meiosis and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In our in silico prediction, we observed that several miRNAs were assigned to gene ontology processes termed as ''GnRH signaling pathway'' (among others). Previous studies have proven the effect of miRNA in GnRH signaling and also the effect of GnRH signaling in miRNA expression patterns (55)(56)(57)(58). The potential gene targets related to this process included kinases and calcium and MAPK signaling pathways, which are involved in FSH and LH production, which in turn could be affecting proper timing for oocyte meiosis and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The real-time PCR thermal profile was as follows: 5 min at 95 °C, 40 cycles of 30 s at 94 °C, 30 s at the corresponding annealing temperature (Tm) and 72 °C for 30 s, followed by 72 °C at 10 min, and 5S ribosomal RNA was used as an internal control for the PCR [17, 34]. The mRNAs primers were designed with Primer 5.0 (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Both miRNAs were demonstrated to target Zeb1, a repressor of Lhb gene transcription (15). FSH secretion has also been shown to be altered by overexpressing or inhibiting miR-361-3p in porcine primary pituitary cells, a miRNA that appeared to be down-regulated by GnRH (16). In neither case was there any evidence that miRNAs played a direct role in GnRH-induced gonadotropin synthesis.…”
mentioning
confidence: 99%